2014
DOI: 10.1186/1477-7827-12-96
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial thickness affects the outcome of in vitro fertilization and embryo transfer in normal responders after GnRH antagonist administration

Abstract: BackgroundThe goal of this study was to assess the association between endometrial thickness on the chorionic gonadotropin (hCG) day and in vitro fertilization and embryo transfer (IVF-ET) outcome in normal responders after GnRH antagonist administration.MethodsA retrospective cohort study was performed in normal responders with GnRH antagonist administration from January 2011–December 2013. Patients were divided into four groups according to endometrial thickness, as follows: <7 mm (group 1), > = 7- < 8 mm (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 15 publications
4
78
0
Order By: Relevance
“…This difference was statistically significant. This finding was comparable with the previous studies 24,25 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This difference was statistically significant. This finding was comparable with the previous studies 24,25 .…”
Section: Discussionsupporting
confidence: 94%
“…The endometrial thickness is routinely assessed prior to the embryo transfer. Different studies have looked at different cut offs of endometrial thickness 24,25 . We compared the success of implantation when the endometrial thickness is less than 8mm and more than 8mm.…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed that the clinical pregnancy rate is <30%, and the live birth rate is <20% in patients with an endometrium thickness of ≤7 mm (21). Additionally, no significant difference has been identified in the clinical pregnancy and implantation rates with endometrial thicknesses in the 8-14 mm range compared with >14 mm (22).…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, endometrial thickness did not significantly vary between the aspirin and placebo‐treated groups and all women had an endometrial thickness between 7 and 13 mm and round up to 97% of them ( n = 58) had an endometrial thickness of >8 mm. Furthermore, different studies have indicated that endometrial thickness of >7 mm is a prerequisite for a successful pregnancy . Our results also confirm the findings of other studies showing no significant differences in endometrial thickness between low‐dose aspirin‐treated women and control group during IVF or ICSI treatment .…”
Section: Discussionmentioning
confidence: 99%